W.E.B. Du Bois : champion of civil rights - Rowh, Mark. (Berkeley Heights, NJ : Enslow Publishers, 1999)
A biography of the noted historian and sociologist who was an important leader of African American protest and helped found the National Association for the Advancement of Colored People.
Includes bibliographical references (p. 124-125) and index.
Keywords: Du Bois, W. E. B. -- 1868-1963 -- Juvenile literature; Du Bois, W. E. B. -- 1868-1963.; National Association for the Advancement of Colored People -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; African American historians -- Biography -- Juvenile literature; Civil rights workers; African Americans -- Biography